Validity of the Wahoo KICKR power trainer and reliability of a 4 km cycle time trial - Zadow, E. K.; Fell, J. W.; Smith, S. T.; Shing, C. M. (Journal of Science and Cycling, 2015)
Purpose: To assess the validity of power and the reliability of a 4 km cycle time trial (TT) using the Wahoo KICKR Power Trainer.